Optimizing Use of Large Databases in Joint Arthroplasty and Orthopaedics. (19th October 2022) - Browne, James A.; Springer, Bryan; Spindler, Kurt P.
Abstract : Abstract: The potential users of "big data" need to consider many factors when choosing whether to use a large observational database for their research question and, if so, which database is the best fit for the scientific question. The first section of this paper, written by Dr. James A. Browne, provides a framework (who, what, where, when, and why?) to assess the critical elements that are included in a large database, which allows the user to determine if interrogation of the data is likely to answer the research question. The next section of this paper, written by Dr. Bryan Springer, focuses on the importance of having an a priori research question before deciding the best data source to answer the question; it also elaborates on the differences between administrative databases and clinical databases. The final section of the paper, written by Dr. Kurt P. Spindler, reviews the concepts of hypothesis-generating and hypothesis-testing studies and discusses in detail the differences, strengths, limitations, and appropriate uses of observational data versus randomized controlled trials.